New optical solitons based on the perturbed Chen-Lee-Liu model through Jacobi elliptic function method - Tarla, Sibel; Ali, Karmina K.; Yilmazer, Resat; Osman, M. S. (Springer, 2022)
In this study, we investigate the perturbed Chen-Lee-Liu equation that represents the propagation of an optical pulse in plasma and optical fiber. The Jacobi elliptic function technique is used for this purpose. As a result, we obtain some new solitary wave solutions such as the Jacobi elliptic function, dark-bright, trigonometric, exponential, hyperbolic, periodic, and singular soliton solutions. To express the pulse propagation of the generated solutions, specific values for the free parameters under conditions are also given.
Keywords: Perturbed Chen-Lee-Liu model; Jacobi elliptic function technique; Analytical solutions